Carbon quantum dots functionalized agarose gel matrix for in solution detection of nonylphenol - Singh, S.; Nigam, P.; Pednekar, A.; Mukherjee, S.; Mishra, A. (Environmental Technology, 2020)
Nonylphenol, an endocrine disrupter, is widely released to the aquatic environment, which is accumulative and extremely toxic to aquatic organisms. Here, we report a simple and cost-effective large-scale green synthesis of water-soluble highly fluorescent carbon quantum dots (CQDs) from marine biowaste (offshore washed algae) which gets quenched strongly in the presence of nonylphenol. These CQDs were around 20-40 nm in size and exhibit fluorescence constantly at 360 nm. The XRD profile depicted the interlayer spacing in the particle as 0.284 nm with a humped peak around 14 degrees showing the amorphous nature of the CQDs. FTIR spectra showed the stretching vibration of the hydroxyl groups (OH), asymmetric and symmetric stretching vibrations of the carboxylate anions (COO-). The fluorescence quantum yield of the CQDs is up to 68% and nonyl phenol detection limit is less than 0.1 µM. Furthermore, the CQDs were found to be stable at a wide pH range which makes it a suitable nonylphenol sensor for a variety of environmental samples. We functionalized these CQDs on an agarose gel matrix to develop a convenient sensor for the rapid detection of nonylphenol.
Keywords: Carbon quantum dots; endocrine disrupter; marine algae; nonylphenol; pollutant